A service evaluation and stakeholder perspectives of an innovative digital minor illness referral service from NHS 111 to community pharmacy - Nazar, Hamde (PLoS One, 2020)
INTRODUCTION: The management of minor conditions represents a significant burden for urgent and emergency care services and reduces the capacity to provide specialist care for higher acuity healthcare need. A pilot Digital Minor Illness Service (DMIRS) was commenced in the North East of England in December 2017 to feasibility test the NHS 111 referral to community pharmacy for patients presenting with minor conditions. OBJECTIVES: A formative evaluation of the service activity data and qualitative investigation of stakeholders involved in the service design, management, delivery and use, aims to present and investigate the service outcomes. METHOD: Routine service activity data was evaluated during Jan–Dec 2018 to investigate the demographics of patients included in the service; the presenting conditions; and how those referrals were managed by community pharmacies. Semi-structured interviews with NHS 111 call handlers, project team members, community pharmacists and patients were undertaken to investigate the design, management, implementation and delivery of the service. RESULTS: 13,246 NHS 111 patient calls were referred to community pharmacy during the evaluative period. The most common presenting conditions were acute pain (n = 1144, 8.6%) and cough (n = 887, 6.7%). A large volume of complaints (47.1%, 6233) were resolved in community pharmacy. Stakeholders explained the structured approach to service design, organisation and implementation facilitated successful delivery and management. Patients reported positive experiences with accessing care via DMIRS. CONCLUSIONS: DMIRS demonstrated that patients could be referred to community pharmacy for the management of minor conditions, shifting a burden away from urgent and emergency care. The service data provides key information for further optimisation of service design, and stakeholder training and awareness. The service was acceptable and valued by patients. Evidence from the DMIRS pilot has been utilised to inform recent national healthcare policy and practice around the management of minor conditions within the urgent and emergency care setting.